The relationship between corporate social responsibility and competitiveness: proposition of a theoretical model moderated by participation in global value chains - Mary Fernanda de Sousa de Melo; Roberta Souza Pião; Willerson Lucas Campos-Silva; José Geraldo Vidal Vieira (Revista Brasileira de Gestão De Negócios, 2019)
Purpose – This paper aims to propose a model that relates Corporate Social Responsibility (CSR), competitiveness, and Emerging Market Enterprises (EMNEs) in Global Value Chains (GVCs) Design/methodology/approach – Extensive literature review and analysis of issues concerning the competitiveness of EMNEs and its relationship with CSR practices, considering their participation in global trade. Findings – The refinement and integration of concepts from the literature review led us to verify that the participation of EMNEs in GVCs moderates the relationship between CSR and competitiveness. In response, we propose a theoretical model resulting in the proposition of six research hypotheses concerning three dimensions of CSR. Originality/value – The proposed model allows for a better understanding of the participation of EMNEs in global trade, considering environmental, social, and strategic dimensions of CSR. It also contributes to the GVC literature by considering global trade from the perspective of EMNEs and adding CSR dimensions in the analysis.